2022
DOI: 10.1128/spectrum.02065-21
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Genetic Alterations in Predicting Ceftriaxone Resistance in Neisseria gonorrhoeae Globally

Abstract: Antimicrobial resistance in Neisseria gonorrhoeae ( N. gonorrhoeae ), the causative agent of gonorrhea, is rising globally. Ceftriaxone is the last remaining antibiotic for empirical treatment of gonorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Due to the increasing international spread of ceftriaxone-resistant strains, there is a need to strengthen international cooperation to monitor and trace the spread of ceftriaxone-resistant clones. 28,29 Infection and Drug Resistance 2023:16 https://doi.org/10.2147/IDR.S396793 DovePress 1445 Spectinomycin, an amino cyclohexanol antibiotic found in Streptomyces, demonstrates strong antibacterial effect on N. gonorrhoeae. In our study, among 1710 clinical strains of N. gonorrhoeae collected in Zhejiang province from 2007 to 2021, only 3 and 1 spectinomycin-resistant strains were found in 2018 and 2019, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing international spread of ceftriaxone-resistant strains, there is a need to strengthen international cooperation to monitor and trace the spread of ceftriaxone-resistant clones. 28,29 Infection and Drug Resistance 2023:16 https://doi.org/10.2147/IDR.S396793 DovePress 1445 Spectinomycin, an amino cyclohexanol antibiotic found in Streptomyces, demonstrates strong antibacterial effect on N. gonorrhoeae. In our study, among 1710 clinical strains of N. gonorrhoeae collected in Zhejiang province from 2007 to 2021, only 3 and 1 spectinomycin-resistant strains were found in 2018 and 2019, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This continued evolution in the pathogen population means that routine surveillance will be a critical part of regularly assessing sequence-based diagnostics that predict resistance phenotype from genotype. 89,121,122…”
Section: Root Mean Squared Errormentioning
confidence: 99%
“…Escape could be achieved through mutations around a probe's target that reduce binding and thus the diagnostic's sensitivity, through dropping the probe's target altogether, or through developing novel resistance mutations or novel combinations of mutations (a particular concern for N. gonorrhoeae , given that it is highly recombinogenic). This continued evolution in the pathogen population means that routine surveillance will be a critical part of regularly assessing sequence‐based diagnostics that predict resistance phenotype from genotype 89,121,122 …”
Section: Framework For Machine Learning Models For Antimicrobial Susc...mentioning
confidence: 99%
“…For example, according to the latest Gonococcal Isolate Surveillance Project (GISP) report 12 ∼15% of surveyed isolates were resistance to penicillin, ∼20% resistant to tetracycline, 33.2% to ciprofloxacin, 5.8% to azithromycin, and 0.3% to cefixime in the United States; and although resistance (≥ 0.25 μg/ml ) was not observed in 2020 to ceftriaxone, isolates with reduced susceptibly have been identified in previous years (2017-2019) as a part of the GISP collection 12 . Additionally, surveillance studies in other countries have identified higher rates of circulating ceftriaxone resistance (e.g., 4.2% in Taiwan 13 , 16% in in Guangdong, China 14 ); with recent observations indicating global dissemination (Japan, China, Europe, Australia, North America and Southeast Asia) of high-level ceftriaxone-resistant strains 1520 . Though the genetic basis of some resistance phenotypes appears to be exclusively encoded by recurrently acquired mutations (i.e., ciprofloxacin resistance is almost always caused by amino acid substitutions in the DNA gyrase subunit A (GyrA S91F and D95G/D95A 21,22 )); the complete genetic bases of other resistance phenotypes is currently not fully described and/or is clearly imparted by multiple additive or epistatically-interacting loci (i.e., penicillin 2327 and azithromycin 22,28 resistance).…”
Section: Introductionmentioning
confidence: 99%